Correction to: Pathogenesis, Clinical Signs and Treatment Recommendations in Brittle Nails: A Review - Marco A. Chessa; Matilde Iorizzo; Bertrand Richert; Jose L. López-Estebaranz; Dimitrios Rigopoulos; Antonella Tosti; Aditya K. Gupta; Nilton Di Chiacchio; Nilton G. Di Chiacchio; Adam I. Rubin; Robert Baran; Shari R. Lipner; et al. (Adis, Springer Healthcare, 2020)
Unfortunately, the co-author name was incorrectly published as "Jose L. López-Esterbaranz" instead of 'Jose L. López-Estebaranz" in the original article. The correct version of author name is updated here. The original article has been corrected.